Pengaruh sudut alur sekat terhadap unjuk kerja menara pendingin (cooling tower) - Ardani, A.; Qiram, I.; Rubiono, G. (Dinamika Teknik Mesin, 2018)
Cooling tower is an equipment that use to decrease water temperature by extracting heat and emitting it to atmosphere. Cooling tower buffle is an important component that effect water flow. This research is aimed to get the effect of cooling tower buffle due to its performance which are range, heat transfer rate and efficiency. The research is done by experiment. Cooling tower buffle are varied in plot angle which are 5o, 10o, 15o dan 20o. Water volume flow rate are varied as 50, 75, 100 and 125 ml/s. Inlet water tempersatur are varied as 50o, 60o and 70oC. The measurements are done for water and air temperature at inlet and outlet points. The result shows that buffle plot angle has effect due to cooling tower performance.